2015
DOI: 10.1097/cin.0000000000000157
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Workload of Computerized Nursing Process in Intensive Care Units

Abstract: The aim of this work was to measure the cognitive workload to complete printed nursing process versus computerized nursing process from International Classification Practice of Nursing in intensive care units. It is a quantitative, before-and-after quasi-experimental design, with a sample of 30 participants. Workload was assessed using National Aeronautics and Space Administration Task-Load Index. Six cognitive categories were measured. The "temporal demand" was the largest contributor to the cognitive workloa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 1 publication
0
22
0
5
Order By: Relevance
“…However, the correlation between extraneous CL and germane CL ( r = 0.003) in our study is different than the original study ( r = −0.19). If a nursing care activity is presented to a nurse in a simple or familiar way, and there is a lower extraneous CL, it seems that the nurse may devote more cognitive resources to germane CL activities (Dal Sasso & Barra, ; Hsieh et al, ). Therefore, extraneous CL and germane CL are expected to be negatively correlated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the correlation between extraneous CL and germane CL ( r = 0.003) in our study is different than the original study ( r = −0.19). If a nursing care activity is presented to a nurse in a simple or familiar way, and there is a lower extraneous CL, it seems that the nurse may devote more cognitive resources to germane CL activities (Dal Sasso & Barra, ; Hsieh et al, ). Therefore, extraneous CL and germane CL are expected to be negatively correlated.…”
Section: Discussionmentioning
confidence: 99%
“…Still, research in Brazil on the comparison of the work of nurses who performed the nursing process using printed material versus computerized material showed that the computerized way contributed to reducing nurses' workload, being a support system for decision making of clinical practice 3 . …”
Section: Introductionmentioning
confidence: 99%
“…Those studies permitted the construction of an information structure available via web (fixed environment) and via mobile devices like a Personal Digital Assistant (PDA) (integrated into the computer system via web) considering the data and clinical information, nursing diagnoses, interventions and outcomes to register nursing care for the documentation of ICU nursing care. 2,6,[13][14] In this study, the CNP for ICUs is structured based on version 2, the most recent version translated to Portuguese by the Portuguese Order of Nurses, in 2011.…”
Section: Introductionmentioning
confidence: 99%